Influence of Household Income on Retention among Pupils in Public Day Primary Schools in Isiolo County, Kenya. - Muchunku, Jackson; Nelson, Jagero; Beatrice, Mburugu (Advances in Social Sciences Research Journal, 2020)
Retention of pupils in primary schools remain a problem in both developed and developing countries (UNESCO, 2011). Socio-economic status characteristics of households, in particular parental income have long been known to be a major determinant of pupils’ retention. The study used correlation research survey design. The population of the study consisted of 4142 that comprises of 546 standard seven teachers and 3594 standard seven pupils in the 91 public day primary schools in Isiolo County. Class seven pupils in the sampled schools were chosen by simple random sampling technique from total number of pupils (3594 pupils). A reliability coefficient of 0.91 for the pupils and 0.92 for the teachers was arrived at. Content validity was ascertained through experts. This study used inferential statistics to analyze the data that was obtained. This study yielded data that required both qualitative and quantitative analysis. Inferential statistics was used to infer sampled data from the population before drawing conclusions. Statistical Package for Social Sciences (SPSS) version 21 aided in data analysis. To establish the overall relationship between the independent and dependent variables, regression models were used. Findings reveal that parental income and pupils’ retention shows positive and significant results at .05 levels. This implies that pupils’ retention is dependent on the income of their parents. Based on the summary of the findings, the household income, was found to be strongly associated with retention of pupils in public day primary schools in Isiolo County. The major conclusion that can be deduced from the findings is that, pupil’s retention in public day primary schools in Isiolo County is strongly associated with household income.